STRATEGY OF ISLAMIC RELIGIOUS EDUCATION TEACHER IN THE DEVELOPMENT OF STUDENT WORSHIP - Wildan Saleh Siregar (Proceeding International Seminar of Islamic Studies, 2022)
Introduction: Prayer is an obligation for every Muslim who has reached puberty and the practice of prayer will be held accountable for the first time in the hereafter. Psychologically, students still need to be given guidance on prayer worship by the teacher. Students at the age of 14 years or equivalent to junior high school students are vulnerable to bad influences, because students are still easily influenced by the environment, so that coaching is determined which emphasizes more on the affective aspect. Literature Review: Besides that, theoretically and prayer materials, so this prayer service is a special concern for teachers to implement prayer practices for students.Method: This research is a qualitative descriptive field research. The research method used in this study were interviews, observation and documentation. The subjects of this study were PAI teachers at SMP Negeri 1 Sipirok. The data analysis used was descriptive qualitative analysis, namely reduction, describing the data and making conclusions based on the description of the data.The results of this study indicate that the PAI teacher's strategy towards students' prayer is carried out through: 1) Using the right approach, 2) providing motivation to students, 3) The teacher directing students to pray, 4) The teacher evaluating students in good prayer activities. Cultivation of student prayer is carried out by the teacher through: 1) Giving advice/guidance to students, 2) The teacher applies habituation in prayer 3) The teacher always reminds students to pray 4) The teacher becomes an example for students 5) The teacher gives rewards / gifts 6) The teacher give punishment.Regarding the obstacles in fostering student prayer services, namely: 1) Teachers, through mass media 2) Schools, the environment around the school can also affect students' prayer services, 3) Students, Like teachers, other factors also come from the student aspect including the nature of the students. owned by students.Keywords: Student Worship Development Strategy